(untitled) (Indian Journal of Animal Production and Management, 2024)
Age of the bull influences the sexual behaviour and quality of semen. The present study was conducted to find out the age window at which the bull shows best reproductive performance. Fifteen Sahiwal bulls were selected and classified into three age groups (n=5, in each group) - G1(2- 3.5), G2 (>3.5-8) and G3 (>8-12) years. The sexual behaviour was recorded at the time of semen collection by CCTV camera at 15 days interval. Scrotal circumference (by scrotal tape) and scrotal surface temperature (by IRT) were also taken at monthly interval. The data so obtained in the experiment was subjected to statistical analysis by one-way analysis of variance (ANOVA) using SPSS software version 26.0 to draw scientific interferences. The results revealed that the mean value of scrotal circumference was significantly (p<0.05) low in G1 as compared to the other two groups. No significant difference was observed among the groups for scrotal surface temperature and scrotal temperature gradient. Most of the sexual behaviour parameters were significantly high in the G2 (>3.5-8) group except for the time to enter arena from preparation site and total number of mountings. Therefore, it can be concluded from this study that sexual behaviour is influenced by age and adult (middle) aged bulls performed better as compared to young and old groups.